Optimization of ultrasound-assisted extraction of phenolics from Asparagopsis taxiformis with deep eutectic solvent and their characterization by ultra-high-performance liquid chromatography-mass spectrometry - Gao, Heqi; Wang, Yuxi; Guo, Zhiqiang; Liu, Yuxin; Wu, Qian; Xiao, Juan (Frontiers in Nutrition, 2022)
Asparagopsis taxiformis is a significant source of phenolics. Owing to the incessant demand of green extraction procedures for phenolics from A. taxiformis, ultrasound-assisted extraction (UAE) using deep eutectic solvents (DESs) was optimized. Among the tested DESs, betaine-levulinic acid afforded the highest total phenolic content (TPC). Moreover, the optimal extraction conditions elucidated from single-factor and response surface methodologies comprised a 52.41 °C ultrasonic temperature, 46.48% water content of DES, and 26.99 mL/g liquid-to-solid ratio. The corresponding TPC (56.27 mg GAE/100 g DW) and antioxidant ability fitted the predicted values. UAE afforded superior TPC and antioxidant abilities with DESs than with traditional solvents. Using UHPLC-MS, 7 phenolic acids, 18 flavonoids, and 2 bromophenols were identified and quantified. DES-UAE afforded the highest phenolic compound number (26) and sum of contents. These results disclose the high extraction efficiency of DES-UAE for A. taxiformis phenolics and provide a basis for the higher-value application of this species.